And then the roof caved in : how Wall Street's greed and stupidity brought capitalism to its knees - Faber, David, 1964- (John Wiley & Sons, 2009)
Explains the events of the previous seven years that planted the seeds for the worst economic crisis since the Great Depression beginning in 2001, when the Federal Reserve embarked on an unprecedented effort to help the economy recover from the attacks of 9/11 by sending interest rates to all time lows.